The effect of calcium phosphate and silk fibroin nanofiber tuning on properties of calcium sulfate bone cements. (11th December 2020) - Xu, Rui; Lian, Xiaojie; Zhao, Liqin; Wei, Yan; Hou, Dingyu; Niu, Baolong; Zhang, Quanyou; Huang, Di; Li, Fen; Gao, Sheng
Abstract: Calcium sulfate (CS) bone cements have been used as bone substitutes for a long time, but their clinical use is currently limited due to their rapid degradation rate and brittleness. This work aimed to study the effect of α-tricalcium phosphate (α-TCP) and silk fibroin nanofibers (SFF) on CS bone cements. The bone cements were prepared from α-CS hemihydrate (α-CSH), calcium sulfate dihydrate (CSD; as a setting accelerator) and varying α-TCP contents (0%, 5%, 10%, 15%, 20% and 25%), with SFF solution or deionized water as the solidification solution at the same liquid/solid ratio. Scanning electron microscopy, particle size distribution, x-ray diffraction and Fourier transform infrared spectroscopy were used to measure the composition and characterize the properties of the materials. The compressive strength, setting time and weight loss rate of samples were also tested. Cytotoxicity was evaluated by a Cell Counting Kit-8 assay. The results suggest that the tuning of α-TCP and SFF has an important role in determining the compressive strength and degradation rate of CS bone cements, and the properties could be changed by varying the content of α-TCP. Moreover, cell experiments showed no toxicity of the samples towards MC3T3 cells. Thus, the materials prepared from α-CSH, CSD, α-TCP and SFF in this work could provide the basis for research into CS-based bone repair materials.